Actual concepts in scaphocephaly : (an experience of 98 cases) - Ciurea, AV (Carol Davila University Press, 2011)
Craniosynostoses are recognized as a group of birth defects that impair the skull structures by early closure of one or more sutures, causing an abnormal cranial shape. Among the "simple" craniosynostoses, (a single closed suture) the most common is scaphocephaly. The 3D CT scan is the most relevant and rapid diagnostic test. The authors present the personal experience of 98 scaphocephaly cases diagnosed and surgically treated in the Neurosurgical Department of "Bagdasar-Arseni" Emergency Hospital during a period of 10 years (2000 – 2009). The procedure of choice was the Stein & Schut (1977) extensive craniotomy that removes the early closed suture. There were no post-operatory death cases and no abnormally closed sutures. The routine use of the craniotome facilitates the lateral osteotomy that allows a normal brain growth and a normal symmetrical skull shape development. The authors advocate for early surgery during the first 6 months of life.